Bioactive polyketides isolated from agar-supported fermentation of Phomopsis sp. CMU-LMA, taking advantage of the scale-up device, Platotex - Emilie Adelin (2018)
Phomopsis sp. CMU-LMA was cultivated on agar-supported fermentation (Ag-SF) using the scale-up prototype Platotex. In total nine compounds were isolated from the ethyl acetate extract of the culture. Among them, compounds LMA-P1, Sch-642305, DHTO and LMA-P2 had already been reported in our previous work on liquid state fermentation. The trihydroxybenzene lactone cytosporone D and dothiorelone A has been recently isolated from Phomopsis and Magnaporthe species. In addition, three compounds were isolated consisting in the reduced methoxy derivative of Sch-642305 (1), a hydroxylated derivative of LMA-P2 (2) and a linear ethyl ester polyketide (3) similar to the previously reported LMA-P3. Antimicrobial activity and inhibition of Escherichia coli DnaG primase were investigated. Cytosporone D inhibited the E. coli DnaG primase, a Gram-negative antimicrobial target, with an IC 50 of 0.25 mM. © 2013 Elsevier Ltd.